A crisis of integration? The development of transnational dyadic trust in the European Union, 1954–2004. (6th December 2012) - Klingemann, Hans‐Dieter; Weldon, Steven
Abstract The healthy functioning and long‐term viability of the European Union (EU) ultimately depend on its citizens finding common cause and developing a shared sense of political community. However, in recent years, scholars and pundits alike have expressed doubts about whether the EU's growing cultural, religious and economic diversity is undermining the development of citizens' shared sense of political community, especially following eastern expansion. In this article, this question is examined using data on a key aspect of political community: transnational dyadic trust. Drawing on a unique set of opinion surveys from the formative years of the EU to the first wave of eastward expansion (1954–2004), the development and sources of dyadic trust among EU Member States is studied. While recognising the importance of diversity for trust judgments in the short‐term, the prevailing viewpoint that it is also a long‐term obstacle to integration is challenged. Instead, it is argued that citizens from diverse cultural and economic backgrounds can learn to trust one another and build a sense of political community over time through greater cooperation and interconnectedness. This theory is tested with data on bilateral trade density, which is seen as a proxy and precursor for other forms of cross‐national interconnectedness. Employing longitudinal models, the article also goes beyond existing research to test the theories over time. The study makes a contribution to the research on European integration, suggesting that over time mutual trust and a shared sense of political community can indeed develop in diverse settings.